Astrocyte control of cerebral blood vessels - MacVicar, Brian (Henry Stewart Talks, 2010)
The regulation of the blood supply of the brain, Functions of astrocytes, Astrocytes all have endfeet, Astrocyte endfeet enwrap all cerebral blood vessels, The modulators of cerebral blood flow, Astrocyte calcium waves cause vasoconstriction, Astrocytes and vascular dynamics, Functional impact of astrocyte induced constrictions, Dilation is more complicated, Can changing levels of O2 and lactate modify vasculature control by astrocytes?, Tissue pO2 levels, Complex regulation of dilation by metabolism, Changing oxygen levels, Astrocytes express both cyclooxygenase -1 and -2, Prostaglandin transporters, Is there a relationship between lactate and PGE2?, Why are vasoconstrictions not observed in low O2?, Brain metabolic state dictates the polarity of astrocyte control over the cerebrovasculature